Teori Kebenaran Pancasila Sebagai Dasar Pengembangan Ilmu - Surajiyo Surajiyo (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Science with its scientific method aims to reach the truth. Because those who areknowledgeable are humans, the truth is not only purely fulfilling the criteria of coherence andcorrespondence but the truth must also be returned to humans. The development of science inIndonesia must also be returned to the Indonesian people, the identity of the Indonesian nation.The theory of truth of Pancasila requires that scientific truth at the same time fulfills the truth ofcoherence, correspondence, and pragmatics. These three things simultaneously complement eachother in scientific work. It means not highlighting or emphasizing one of them. For thedevelopment of science in Indonesia, the truth value of Pancasila must be used as the basis.The method in this research is the descriptive method, which is a literary discussion,especially literature that discusses the problem of science, the theory of truth in science, and theproblem of Pancasila both scientifically and philosophically. In this method, classification, dataprocessing, and conclusions are carried out. The data collected is qualitative data then processedby analytical and reflective methods, equipped with the 'verstehen' method.